An open-source molecular diagnostic platform approach for outbreak and epidemic preparedness - Devy M. Emperador; Laura T. Mazzola; Cassandra Kelly-Cirino (AOSIS, 2020)
Background: Diagnostic development for outbreak pathogens has typically followed a disease-specific reactive rather than proactive response. Given the diversity of outbreak pathogens, particularly those prioritised by the World Health Organization Research and Development Blueprint, a more flexible and proactive approach to epidemic preparedness is needed to expand access to critical molecular diagnostic tests in peripheral and resource-constrained deployment settings. Objective: New and more sustainable directives are needed to spur the development of high-quality products, particularly for epidemics more often found in low- and middle-income countries. To leverage and de-risk the development process, we present the benefits and challenges of an open-source business model for co-development of molecular diagnostic tests for decentralised settings. Methods: We identify key outbreak pathogens that are available only for testing in high infrastructure laboratories and compare in-country installed base platforms that could be leveraged for menu expansion. Key strengths and challenges for development are highlighted for both platform and assay developers, with discussion of how to leverage and de-risk the process through an open-source development model. Results: Depending on the specific partner strengths, options for partnership roles are presented. The proposed open-source business model addresses the particular challenges in the detection of outbreak- and epidemic-prone pathogens in low- and middle-income countries, reduces development and deployment risks to support outbreak response, strengthens diagnostic capacity and creates a viable market for product developers. Conclusion: We hope this model for a collaborative and open-source approach for molecular diagnostics serves to encourage stakeholders to consider co-development partnerships to improve outbreak preparedness and epidemic/pandemic response.